Experimental Study on Fragmentation Behavior of Specimen with Rockbolts. (31st October 2020) - Dong, Enyuan; Wang, Weijun; Zhao, Zhiwei; Peng, Wenqing; Yuan, Chao
Abstract : The effect of rockbolt density on fractured specimens and the distribution law of fragments were studied using the fractal method. The results show that with the increase of rockbolt density, the strength of specimens is improved. Its degree of fragmentation is increased, but the average size of fragments is decreased. The fragmentation and surface fractal dimensions are increased, their difference value is 1 in theory, but the value is slightly less than 1 in practical application due to the uncertain factors such as anisotropy of specimen. There is a positive correlation between the deformation of surrounding rock and its fractal dimension. The surface fractal dimension of surrounding rock can give a quantitative description of its degree of fragmentation and can give a comprehensive reflection to the roof stability. The support mechanism of rockblots can be understood as improving the probability of refragmentation of fragments, making its distribution gradation close to the optimal one with minimum porosity, thus reducing the deformation of surrounding rock.